2022
DOI: 10.3389/fnut.2022.947706
|View full text |Cite
|
Sign up to set email alerts
|

Extraction, isolation, structural characterization, and antioxidant activity of polysaccharides from elderberry fruit

Abstract: The isolation, purification, and antioxidant activity of polysaccharides extracted from elderberry fruits were studied. Two neutral polysaccharides (EFP-0 and EFP-1) and three acidic polysaccharides (EFP-2, EFP-3, and EFP-4) were isolated from elderberry. EFP-0, EFP-1, EFP-2, EFP-3, and EFP-4 all contain arabinose, galactose, glucose, and mannose, with molecular weights of 1.7981 × 106, 7.0523 × 106, 7.7638 × 106, 4.3855 × 105, and 7.3173 × 105 Da, respectively. Structural characterization showed that the back… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 78 publications
(97 reference statements)
0
6
0
Order By: Relevance
“…Furthermore, the proton and carbon signals for other residues were assigned through the analysis of HSQC combined with 1 H-1 H COSY spectra. the H2/C2-H5/C5 values of residue A were 5.03/107.31, 4.07/81.03, 3.96/76.34, 4.15/82.07, and 3.75/60.99 ppm [45]. The H2/C2-H5/C5 values of residue B were 5.17/106.35, 4.24/81.34, 3.89/76.68, 3.98/83.83, and 3.98/83.83 [46].…”
Section: Nmr Spectra Analysismentioning
confidence: 92%
“…Furthermore, the proton and carbon signals for other residues were assigned through the analysis of HSQC combined with 1 H-1 H COSY spectra. the H2/C2-H5/C5 values of residue A were 5.03/107.31, 4.07/81.03, 3.96/76.34, 4.15/82.07, and 3.75/60.99 ppm [45]. The H2/C2-H5/C5 values of residue B were 5.17/106.35, 4.24/81.34, 3.89/76.68, 3.98/83.83, and 3.98/83.83 [46].…”
Section: Nmr Spectra Analysismentioning
confidence: 92%
“…However, its extraction process is time-consuming and low in yield [25] . In contrast, physical-assisted extraction methods, such as pressurized hot water extraction (PHWE), ultrasonic-assisted extraction (UAE) and microwave-assisted extraction (MAE), can extract polysaccharides more efficiently and increase the yield of sea buckthorn crude polysaccharides while ensuring environmental protection [26][27][28][29][30][31] . Nevertheless, care should be taken to control a reasonable temperature range, as high temperature may lead to degradation of polysaccharides, leading to a lower extraction yield.…”
Section: Extraction Methodsmentioning
confidence: 99%
“…The sea buckthorn polysaccharides can be categorized into neutral and acidic polysaccharides due to the content of uronic acid [109] . Wei et al [27] isolated the crude polysaccharide of sea buckthorn to obtain three polysaccharide fractions, including two acidic polysaccharides and one neutral polysaccharide. It was found that the antioxidant properties of the acidic polysaccharides SBP-III and SBP-II were significantly higher than those of the neutral polysaccharide SBP-I.…”
Section: Content Of Uronic Acidmentioning
confidence: 99%
“…[22] Although much progress has been made in the study of methods for the extraction, isolation and purification of EFPs, it is necessary to continue the search for simpler, more efficient and cheaper methods for the large-scale production of high-quality EFPs in the pharmaceutical and functional food industries. [23] Since EFP has high biological activity, it is important to establish an efficient and economical extraction method. At the same time, attention should be paid to improving the purity of polysaccharides, obtaining homogeneous polysaccharides, and studying their physicochemical properties and bioactivities in order to maximise the value of EFP Since EFP has high biological activity, it is important to establish an efficient and economical extraction method.…”
Section: Clinical Application and Prospect Of Mycelial Polysaccharidesmentioning
confidence: 99%